Anesthetic management of an emergency caesarian delivery in a 61 year 8 month old Primigravid patient with 33+ wks pregnancy (IVF, twin) with Diabetes Mellitus with Hypertension with Hypothyroidism and Mild aortic stenosis - Mahmood, Wahiuddin; Ali, SM; Islam, Md Quamrul; Das, Debasish; Das, Basudeb; Khan, Tasmia (Journal of the Bangladesh Society of Anaesthesiologists, 2020)
Physiologic changes of pregnancy uniquely influence anesthesia for caesarian delivery. Aging is also anuniversal and progressive physiological phenomenon clinically characterized by degenerative changesin both the structure and the functional capacity of organs and tissues. For an anesthesiologist the casebecomes more challenging when the patient has multiple comorbidities such as Diabetes Mellitus,Hypertension, Hypothyroidism and Mild Aortic stenosis. We report an emergency caesarian delivery inthe case of a 61 year 8 month old woman who was diagnosed as 33+wks Pregnancy (IVF, TWIN) withDM (Insulin) with Hypothyroidism on medication with Hypertension on medication with Mild aorticstenosis. Emergency caesarian delivery of this patient was necessary due to oligohydramnios with laborpain and fetal distress. The delivery was successfully performed under SAB and patient recovered withoutany complication. JBSA 2020; 33(1): 43-45